The Munk-Cartwright Method for Tidal Prediction and Analysis - Franco, A. Dos Santos (The International Hydrographic Review, 2015)
In the course of a Tidal Symposium held in Paris in May 1965 Munk and Cartwright presented a new method for tidal prediction and analysis to which they gave the name "response method" Others proposed to call this new solution the "convolution method" since the tidal heights are obtained by a weighted sum of terms of the equilibrium tide. This last name seems the more appropriate one, but this interesting method could also be called the “ generalised Laplace method The paper [1] presented by these two eminent scientists is of an extremely high level and they end it with a quotation from Hilaire Belloc (1925) : "When they pontificate on the tides it does no great harm, for the sailorman cares nothing for their theories, but goes by real knowledge." However I think that it is possible to explain the method in a somewhat less sophisticated way, and also to extract from their article a little of this "real knowledge" so dear to sailors. This is the aim of the present article.